Kertas Saring sebagai Media Transpor Darah untuk Pemeriksaan Antibodi Rabies - Retno Wijayanti; Retno Damayanti; Sri Murtini (Jurnal Sain Veteriner, 2019)
Rabies is a zoonotic disease. Rabies protection level detection was performed using antibody titration. Blood sampling activities in the field require special handling to avoid blood lysis, the sample delivery requires a cold chain with a stable temperature. Alternative method forwhole blood sample delivery using filter paper were carried out on 48 samples from susceptible animals (dogs and cats) transpored through the Soekarno Hatta Agricultural Quarantine Center. This  study was designed to investigate the feasibility of filter paper sampling of blood at temperature of 26 °C to detect of rabies antibodies using indirect method of ELISA. The results of statistical analysis of  Randomized Block Design and Tukey's test showed that the antibody titres of whole blood extracted from filter paper diluted in the PBS T 100 μl were equivalent to antibody titres of serum. Assesment of filter paper capability has sensitivity and specificity as much as 96% and 76%, positive predictive value of 67%, negative predictive value of  94% and reliability level of filter paper were 0.5 is moderate category. This indicates that the filter paper can be used as an alternative method of blood transport medium for rabies ELISA test.